Unilateral Resistance Training Can Be Tailored Using Lifting Velocity in Breast Cancer Patients - Franco-López, Francisco; Hernández-Belmonte, Alejandro; García-Segura, Ana Maria; Martínez-Cava, Alejandro; Pallarés, Jesús G.; Courel-Ibañez, Javier (International Journal of Sports Medicine, 2025)
We aimed to study the feasibility of velocity-based training (VBT) to individualize load and velocity loss (VL) during unilateral bench press (UBP) in breast cancer survivors, as well as to analyze possible asymmetries between their operated and non-operated limbs. Twelve post-surgical breast cancer survivors performed progressive UBP assessments with each arm up to one-repetition maximum (1RM) to determine individual load–velocity profiles. Mean propulsive velocity and mean velocity were modelled against%1RM using second-order polynomial regressions. In separate sessions, participants performed two sets per arm at 60–80% 1RM until reaching 40% VL. Repetition counts were compared between limbs. Strong associations were observed between velocity metrics and%1RM on both the operated and non-operated sides (R2≥0.92). Differences in velocity at matched relative loads were trivial (≤ 0.01 m/s, p≥0.448). The number of repetitions performed until reaching the VL threshold did not significantly differ between limbs (≤ 3 repetitions, p≥0.072). VBT is a feasible and effective method for individualized load and volume prescription during unilateral resistance training in breast cancer survivors. Load–velocity profiles and fatigue responses were symmetrical between operated and non-operated limbs, supporting the integration of VBT into rehabilitation and return-to-function programs in this population.
Keywords: strength training; bar velocity; intensity; imbalance; asymmetry